Up-conversion material luminous intensity enhancing method based on composite film and application

Through the synergistic effect of the precious metal composite thin film structure and NaGdF4:Er3+/Yb3+ luminescent crystal, the luminescent intensity of the upconverted material is significantly enhanced by the plasma resonance effect, solving the problem of insufficient effect of single precious metal layer, and is suitable for practical applications such as solar panels.

CN119307260APending Publication Date: 2025-01-14SOUTHEAST UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411204968.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-30
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The luminescence intensity enhancement effect of existing composite film-type upconversion materials is limited, and the plasma resonance effect of the single precious metal layer is insufficient, making it difficult to meet the growing demand for luminescence intensity.

Method used

The silver film and gold nanorod composite film were prepared by vacuum evaporation and spraying technology, and NaGdF4:Er3+/Yb3+ luminescent crystals were uniformly coated on it, controlling the annealing temperature and concentration to optimize the working conditions of the composite film. , luminous intensity is enhanced by using plasma resonance effect.

Benefits of technology

The luminescence intensity of upconverted materials is significantly improved, especially the green intensity at wavelengths of 521 nm and 540 nm is enhanced by 3.34 times and 4.1 times, and the red intensity at 653 nm is enhanced by 3.64 times, which is suitable for practical applications such as solar panels. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119307260A_ABST
    Figure CN119307260A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of optical materials, and discloses an up-conversion material luminous intensity enhancing method based on a composite film and application, and the method comprises the following steps: plating a layer of silver film on a glass pole piece through a vacuum evaporation technology, heating on a heating stage, spraying by adopting a gold nanorod solution to obtain a gold-silver composite film, and drying to obtain the up-conversion material luminous intensity enhancing method based on the composite film. And uniformly coating a layer of NaGdF4: Er < 3 + > / Yb < 3 + > nanocrystals on the gold-silver composite film by using a spin-coating method. According to the method, the working temperature of the composite film is reduced, the luminous intensity of the up-conversion material is effectively enhanced through the plasma resonance effect of precious metal, and the composite film type structure is also beneficial to being used in practical engineering such as a solar panel.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of optical materials, and in particular relates to a method for enhancing the luminous intensity of an up-conversion material based on a composite film and an application thereof. Background Art

[0002] With the continuous exploration and application of optical phenomena, from early natural light sources to contemporary advanced laser technology, human beings have become more mature in the generation and application of light. Upconversion luminescent materials that work using the anti-Stokes effect can convert low-energy infrared light into higher-energy visible light. Due to their unique optical properties, upconversion luminescent materials have shown broad application prospects in many cutting-edge scientific and technological fields such as biomedical imaging, solar energy technology, and safety signs.

[0003] In order to meet the growing demand for luminous intensity, in recent years researchers have proposed using surface plasmon resonance of precious metal nanoparticles to enhance the luminous efficiency of upconversion nanophosphors.

[0004] Since thin-film upconversion materials can be conveniently applied to practical scenarios such as solar panels, they have become a research direction that has attracted much attention. However, current research on composite thin-film upconversion materials is still insufficient, and the plasma resonance effect generated by a single noble metal layer has extremely limited enhancement effect on upconversion materials. There is an urgent need for a method to further enhance the luminescence intensity of upconversion materials. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a method and application of enhancing the luminescence intensity of upconversion materials based on composite thin films, which enhances the luminescence intensity of upconversion materials through the synergistic effect of multiple precious metal layers, controls the annealing temperature to change the morphology of evaporated nanosilver, and sprays gold nanorod solutions of different concentrations to further optimize the working temperature of the composite film and NaGdF4:Er 3+ / Yb 3+ Upconversion luminescence intensity.

[0006] The technical solution provided by the present invention is as follows:

[0007] A method for enhancing the luminous intensity of an upconversion material based on a composite film comprises the following steps: coating a layer of silver film on a glass electrode by vacuum evaporation technology, heating on a hot table for the first annealing treatment, spraying with a gold nanorod solution to obtain a gold-silver composite film, and then evenly coating a layer of NaGdF4:Er on the gold-silver composite film by spin coating. 3+ / Yb 3+ Glowing crystals.

[0008] Furthermore, the NaGdF4:Er 3+ / Yb3+ The preparation method of the luminescent crystal comprises: mixing gadolinium acetate, ytterbium acetate, erbium acetate and aluminum ions, heating the obtained mixed solution in an oil bath, adding a solution containing NH4F, NaOH and methanol to carry out a high pressure reaction, centrifugally washing and drying, and performing a second annealing treatment to obtain NaGdF4:Er 3+ / Yb 3+ Glowing crystals.

[0009] Furthermore, the proportion of aluminum ions in the mixed solution is 13-17 at.%.

[0010] Furthermore, the Gd 3+ , Yb 3+ , Er 3+ The molar ratio is 75~80:20:2.

[0011] Further, oleic acid and octadecene are added to the mixed solution, and then heated in an oil bath at a temperature of 130-170° C. for a heating time of 20-30 min.

[0012] Furthermore, the conditions of the high pressure reaction are 180-220° C., time 6-10 hours, and pressure 15-16 MPa.

[0013] Furthermore, the first annealing treatment has a temperature of 70-90° C. and a time of 0.5-1.5 h; the second annealing treatment has a temperature of 240-260° C. and a time of 1-3 h.

[0014] Furthermore, the concentration of the gold nanorod solution is 0.15-0.25 mg / ml.

[0015] The present invention also provides an up-conversion material based on a composite film, which is prepared by the above method.

[0016] The present invention also provides application of the above-mentioned composite film-based up-conversion material in solar panels.

[0017] Beneficial Effects

[0018] The present invention proposes a technology for enhancing the luminescence intensity of up-conversion materials by using the plasma resonance effect of a precious metal composite film. The up-conversion material prepared by the method reduces the working temperature of the composite film, and effectively enhances the luminescence intensity of the up-conversion material by the plasma resonance effect of the precious metal. The composite film structure is also conducive to the use of practical projects such as solar panels. Compared with the single precious metal enhancement scheme of the prior art, the present invention enhances the luminescence intensity of the up-conversion luminescent material NaGdF4 by 3.34 times and 4.1 times at wavelengths of 521 nm and 540 nm, respectively, and enhances the red light by 3.64 times at 653 nm. The reason is that the plasma resonance peak of the metal composite film and the absorption peak of the up-conversion luminescent material are mutually coupled and doped with Al3+ ions. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 Schematic diagram of the film structure of the technology described in the present invention.

[0020] Figure 2 15 at.% Al 3+ Doped NaGdF4:Er 3+ / Yb 3+ Phase analysis diagram of nanocrystals: (a) SEM image; (b) particle size distribution diagram.

[0021] Figure 3 For different concentrations of Al 3+ Doped NaGdF4: Er 3+ / Yb 3+ Enlarged spectrum of the main diffraction peak of nanocrystal XRD.

[0022] Figure 4 To dope different concentrations of Al 3+ NaGdF4:Er 3+ / Yb 3+ Fourier transform infrared (FT-IR) spectrum of nanocrystals.

[0023] Figure 5 To dope different concentrations of Al 3+ NaGdF4:Er 3+ / Yb 3+ Upconversion fluorescence image of nanocrystals.

[0024] Figure 6 The SEM images of the 10 nm Ag film obtained in the implementation of the present invention after annealing at different temperatures; (a) RT, (b) 80 °C, and (c) 100 °C.

[0025] Figure 7The absorption spectra of the Ag thin film at different annealing temperatures (RT, 70°C, 80°C, 90°C, 100°C) in the implementation of the present invention.

[0026] Figure 8 The up-conversion luminescence performance analysis diagram of UC and Ag / UC in the specific implementation of the present invention; (a) up-conversion fluorescence spectrum; (b) enhancement factor diagram.

[0027] Fig. 9 The Au / Ag phase and optical performance analysis diagram in a specific embodiment of the present invention; (a) SEM image; (b) absorption image.

[0028] Fig.10 The up-conversion luminescence performance analysis diagram of UC, Ag / UC, and Au / UC in the specific implementation of the present invention; (a) up-conversion fluorescence spectrum; (b) enhancement factor diagram.

[0029] Fig.11 This is an analysis diagram of the up-conversion luminescence performance of UC, Ag / UC, Au / UC, and Ag / Au / UC in the specific implementation of the present invention.

[0030] Fig.12 Spectra of photothermal effects of UC, Ag / UC and Ag / Au / UC in the specific implementation of the present invention.

[0031] Fig.13 These are thermal imager images in the specific implementation of the present invention; (a) UC, (b) Ag / UC, (c) Ag / Au0.2 / UC, (d) Ag / Au0.4 / UC, (e) Ag / Au0.6 / UC. DETAILED DESCRIPTION

[0032] The present invention will be further explained below in conjunction with the accompanying drawings and specific embodiments.

[0033] Example 1

[0034] 1. Preparation of NaGdF4:Er 3+ / Yb 3+ Nanocrystals: The first step is to press gadolinium acetate, ytterbium acetate, and erbium acetate into Gd 3+ :Yb 3 + :Er 3+ = 78:20:2 molar ratio, and then additional AlCl3·6H2O was added to make it contain 15 at.% Al 3+ions. Put all of it into a beaker and add 17 ml of oleic acid and 18 ml of octadecene, and heat it in an oil bath at 150 °C for 20-30 min. Pour the mixed solution into a container containing 0.8888 g of NH4F, 0.12 g of NaOH and 5 ml of methanol solution, and carry out a high-pressure reaction (15-16Mpa) at 200 °C for 8 hours. Subsequently, wash alternately with deionized water and anhydrous ethanol and repeat the centrifugation operation to thoroughly clean the sample. Then dry it at 80 °C for 1 h, and then anneal it at 250 °C for 2 h. The nanocrystals obtained by scanning electron microscopy Figure 2 (a) 15 at.% Al 3+ Doped NaGdF4:Er 3+ / Yb 3+ SEM image of these nanocrystals. The particle size of these nanocrystals is relatively uniform. Figure 2 (b) shows their particle size statistical distribution, with an average particle size of approximately 33 nm.

[0035] 2. Vacuum evaporation coating of silver film: A 10 nm silver film is coated on a glass substrate by vacuum evaporation technology. First, fix the substrate on the sample holder of the vacuum evaporation system. Draw the vacuum to a high vacuum state to reduce the interference of gas molecules. Use a tungsten boat as an evaporation source, heat it to an appropriate temperature to evaporate the silver particles, control the rate during the evaporation process, ensure that the silver film is evenly and accurately deposited on the glass substrate, and then anneal it at 80 °C for 1 h.

[0036] 3. Spraying of gold nanorods: This experiment uses the gold nanorod solution produced by Zhongke Keyou, with a diameter of 10nm, a length of 55nm, and a concentration of 0.8mg / ml. Use a pipette to dilute it to 0.2mg / ml. Place the Ag nanofilm prepared in the above steps on a hot table and heat it to 80 °C. After the temperature is constant, use a spray gun to evenly spray it.

[0037] 4. Spin coating of up-conversion luminescent crystals: Use a magnetic stirrer to spin coat the prepared NaGdF4:Er 3+ / Yb 3+ The nanocrystals were dispersed in isopropanol solvent, and a layer of NaGdF4:Er was uniformly coated on the gold-silver composite film using spin coating. 3+ / Yb 3+ Luminescent crystal. Set the spin coater speed to 2000~3000 rpm and the time to 30~60 s. The spin-coated substrate is dried naturally at room temperature.

[0038] 5. Optical performance testing and analysis: The prepared nanomaterials and composite films were characterized and tested by X-ray diffraction, transmission electron microscopy, spectrophotometer, fluorescence spectrometer and FLIR. Figure 6 As shown, compared with the single UC film, the green light intensity of the Au / UC composite film at 521 nm and 540 nm wavelengths is enhanced by 1.04 times and 2.03 times, respectively, while the red light at 653 nm is enhanced by 1.34 times. The green light intensity of the Au / UC composite film at 521 nm and 540 nm wavelengths is enhanced by 1.04 times and 2.03 times, respectively, while the red light at 653 nm is enhanced by 1.34 times. The up-conversion luminescence intensity of the Ag / Au / UC composite film is enhanced by 4.34 times and 4.87 times at 521 nm and 540 nm wavelengths, respectively, while the red light at 653 nm is enhanced by 3.17 times compared with the single UC layer. It can be seen that gold and silver precious metals have a great influence on the up-conversion luminescence intensity of NaGdF4:Er 3+ / Yb 3+ All of them have some gain, and the synergistic gain effect of the composite film is better.

[0039] Example 2

[0040] Exploring NaGdF4:Er 3+ / Yb 3+ Al 3+ Doping ratio

[0041] Synthesis of NaGdF4:Er using a solvothermal method 3+ / Yb 3+ Nanocrystals, and Al 3+ Doping, doping concentration range from 0 to 17.5 at.%. During the synthesis process, the Al 3+ The molar ratio of Ag / MgO was used to explore its effect on the phase, morphology and luminescence properties of nanocrystals. Al was uniformly coated on the Ag / dielectric layer by vacuum method. 3+ The doped UC layer was used to study the effect of different dielectric layer types and thicknesses on the luminescence performance. 3+ The upconversion luminescence performance of doped nanocrystals was recorded and compared with different Al 3+ The luminescence intensity and fluorescence lifetime under the doping ratio. Through the measurement of fluorescence spectrometer, when other variables remain constant, Al 3+ When the doping concentration in the lattice reaches the optimal value of 15 at.%, the optimal luminescence intensity can be obtained due to a slight contraction of the lattice volume. This is because Al 3+ Ions are doped into the NaGdF4 lattice, making Er 3+ The decrease in the symmetry of the crystal field around the ions increases the probability of electron transitions, thereby changing the luminescence intensity.

[0042] like Figure 3 As shown, by magnifying the main diffraction peak of the XRD spectrum, with the Al 3+ As the doping concentration increases, the position of the main diffraction peak (110) changes significantly. 3+ When the doping concentration increases from 0 to 15 at.%, the main diffraction peak moves to a larger angle, that is, it redshifts. 3+ When the doping concentration continues to increase to 17.5 at.%, the main diffraction peak moves to a smaller angle, showing a blue shift. 3+ When the doping concentration reaches 15 at.%, the shift amplitude of the main diffraction peak is most significant.

[0043] With Al 3+ With the gradual increase of concentration, Al in NaGdF4 3+ The ion content increases and Gd 3+ The ion content is reduced accordingly. 3+ The radius of the ion (53.5 pm) is smaller than that of Gd 3+ The radius (93.8 pm) at lower Al 3+ At the doping concentration, Al 3+ Ions are more likely to replace Gd 3+ ions enter the matrix lattice. This substitutional doping causes the lattice to shrink and the grain volume to decrease, causing the main diffraction peak to move to a larger angle. 3+ When the doping concentration of Al 3+ Ions enter the lattice mainly in an interstitial manner, and the grain volume increases accordingly, so the main diffraction peak shifts to a smaller angle. This change reflects a subtle adjustment of the lattice structure and is extremely sensitive to doping concentration. Figure 5 To dope different concentrations of Al under 980 nm, 0.6 W laser diode excitation 3+ NaGdF4:Er 3+ / Yb 3+ Upconversion fluorescence spectrum of nanocrystals. From the spectrum, it can be observed that Er 3+ The three emission bands of 2 H 11 / 2 → 4 I 15 / 2 and 4 S 3 / 2 → 4 I 15 / 2 The energy level transition can produce green light emission bands at 522 and 541 nm; 4 F 9 / 2 → 4 I 15 / 2The energy level transition of can produce a red light emission band at 655 nm. According to this figure, we can see that as Al 3+ With the continuous increase of doping concentration, the up-conversion luminescence intensity also shows a trend of increasing first and then decreasing. 3+ When the doping concentration reaches at.15%, the red and green light luminescence intensity reaches the maximum value, which is different from that without Al doping. 3+ Compared with the samples with , the maximum luminous intensity of red and green light increased by 5.7 times and 5 times respectively. 3+ The up-conversion luminescence intensity is greatly enhanced because Al 3+ Ions are doped into the NaGdF4 lattice, making Er 3+ The symmetry of the crystal field around the ions decreases, increasing the possibility of electron transition, thereby changing the luminescence intensity. 3+ When 3+ It is easy to enter the lattice by substitutional doping to increase the luminescence intensity. 3+ When the doping is higher than at.15%, more and more Al 3+ Occupies the position of the lattice gap, which increases the symmetry of the lattice and makes Er 3+ The local crystal field symmetry around the electrode also gradually increases, which eventually leads to a gradual decrease in the luminescence intensity. In addition, high concentration doping leads to an increase in surface adsorption groups, which also reduces the luminescence intensity from another aspect.

[0044] In Example 2, NaGdF4:Er3+ / Yb3+ nanocrystals were doped with 15 at.% Al 3+ The upconversion luminescence intensity was observed to be significantly increased by nearly 5 times. This effect is better than that of undoped Al 3+ Comparative experiment of Al doping 3+ This causes the lattice to shrink, reducing Er 3+ The symmetry of the crystal field around the ions increases the probability of electron transitions, thereby significantly enhancing the luminescence intensity.

[0045] Example 3

[0046] Investigate the influence of annealing temperature and thickness on the SPR characteristics of silver nanofilm layer

[0047] The vacuum preparation was carried out by combining a mechanical pump and a molecular pump to reduce the pressure in the evaporation chamber to 2.0 × 10 -4Pa or less to achieve a high vacuum state suitable for coating. During the evaporation process, the current is set between 85 and 92A to ensure that the silver material can evaporate evenly and stably. At the same time, the temperature of the substrate is controlled at room temperature and the rotation speed is set to 20 revolutions per minute to promote uniform deposition of the film. Using evaporation coating technology, the silver material is deposited on the substrate, and the film thickness is precisely controlled to 10 nm by a crystal oscillator.

[0048] like Figure 7 As shown in the figure, the Ag nanoparticle film was annealed at different temperatures (room temperature, 70 °C, 80 °C, 90 °C and 100 °C) to analyze its effect on the SPR absorption characteristics. Through annealing, the particle size of the Ag nanoparticles increased, and the distance between the particles also increased, which affected its SPR characteristics and caused obvious changes in the absorption peak in the UV-visible spectrum. In particular, the change in the shape of the nanoparticles has a significant effect on the resonant absorption wavelength. The wavelength obtained by the spectrophotometer Figure 7 It can be seen that annealing treatment makes the shape of Ag nanoparticles tend to be spherical, and its shape factor F gradually approaches 1 / 3, and the particle dispersion is enhanced. These changes reflect the enhancement of the interaction between nanoparticles and the change of the local dielectric environment. The absorption peak of Ag nanoparticles annealed at 80°C is the highest, reaching a level of 0.75, which is much higher than 0.6 before annealing. These changes lead to changes in the plasma resonance absorption characteristics, and the annealing temperature is analyzed by Maxwell-Garnet (MG) theory. In this theoretical framework, the interaction between nanoparticles and its influence on the effective dielectric constant become the key to the analysis. The specific expression is as follows:

[0049] Formula (1)

[0050] ε in the formula m is the dielectric constant of the surrounding medium of the metal crystal nanoparticle, ε eff is the effective dielectric constant and is the dielectric constant. ε is the shape factor related to the dielectric constant, F is the shape factor, ε is the dielectric constant of the entire material, and q is the volume ratio occupied by the nanoparticles, also known as the filling rate, which can be expressed by the formula:

[0051] Formula (2)

[0052] It is calculated that in this formula, q is the filling rate, V represents the volume of the particle, h is the height of the particle, and the lattice parameter or the average distance between particles is l. Here, the shape influence factor F is 1 / 3 for common spherical particles. The F value of ellipsoidal particles is related to their eccentricity e.

[0053] Annealing treatment increases the size of Ag nanoparticles and makes them dispersed evenly. According to the Maxwell-Garnett equation, the increase in the distance between particles will lead to a decrease in the filling rate q, which is consistent with the effective dielectric constant ε of the particles. eff Directly related, ε eff It gradually decreases with the decrease of q. The low effective dielectric constant will lead to an increase in the exciton binding energy of the nanomaterial, because the electric polarization in the medium increases the Coulomb interaction between the electrons and holes inside it, which further leads to the blue shift of the emission spectrum. In the preparation process of Ag / UC composite film, the Ag nanoparticle film is treated with a specific annealing temperature (80°C), which is crucial for optimizing the shape and distribution of the nanoparticles. After treatment, the nanoparticles tend to be spherical and the dispersion is enhanced, which significantly improves the SPR characteristics. The annealed Ag nanoparticle film shows a significant increase in the absorption peak in the UV-visible spectrum, and the resonance peak intensity reaches 1.25 times that before annealing, which proves the effectiveness of this step.

[0054] Example 4

[0055] Exploring the influence of silver nanofilm on the luminescence intensity of upconversion materials

[0056] The Ag / UC film and UC film were analyzed using a fluorescence spectrometer. Figure 8 As shown in the figure, under the excitation of a 980 nm, 0.5 W laser diode, the Ag / UC composite film exhibits a significant luminescence enhancement effect. The introduction of Ag nanoparticles into the UC film can excite surface plasmon resonance at a specific wavelength. This resonance effect can locally enhance the electromagnetic field intensity near the film, thereby absorbing more light energy and improving the efficiency of upconversion fluorescence. This is because the SPR effect makes the fluorescence emission stronger by increasing the probability of excited state electrons in the UC film. Compared with the UC film alone, the green light intensity of the Ag / UC composite film at 521 nm and 540 nm wavelengths is enhanced by 1.04 times and 2.03 times, respectively, while the red light at 653 nm is enhanced by 1.34 times.

[0057] Example 5

[0058] To investigate the effect of spraying different concentrations of gold nanorod solution on the above nanosilver film on the SPR characteristics

[0059] Scanning electron microscopy (SEM) was used to observe that the surface of the 10 nm thick silver nanofilm annealed at 80 °C was uniformly sprayed with 0.2 mg / ml gold nanorod solution, such as Fig. 9As shown in (a), the gold nanorods are evenly distributed on the surface of the silver nanofilm, and their particle size is significantly smaller than that of the silver nanoparticles. The samples were further analyzed, and the absorption spectra of the silver films treated with different concentrations of gold nanorod solutions were measured by spectrophotometer at the same temperature, as shown in Figure 2. Fig. 9 (b) shows the absorption diagram of the silver nanofilm after annealing at 80 °C and uniformly spraying 0.2 mg / ml, 0.4 mg / ml, and 0.6 mg / ml of gold nanorod solution on the surface.

[0060] Since the dielectric constant of gold is greater than that of silver, as the concentration of the gold nanorod solution increases, the overall dielectric constant of the composite film also increases, and the increase in the dielectric constant leads to a red shift in the absorption peak. The dielectric constant of gold is greater than that of silver, which means that the polarizability of gold is higher, thus being able to more strongly affect the overall dielectric constant of the composite film. Using a variation of the Maxwell-Garnett theory, we can describe the process of gold nanorods as a filler material to enhance the dielectric constant of the silver nanofilm, as follows:

[0061] Formula (3)

[0062] In the formula is the effective dielectric constant of the composite material. is the dielectric constant of the silver nanofilm. is the dielectric constant of the gold nanorods. is the volume fraction of gold nanorods in the composite material.

[0063] because > , increasing the content of gold nanorods (i.e. increasing ) will lead to This increase is accompanied by becomes more significant.

[0064] The resonance peak intensity of the composite film is significantly higher than that of the single silver film, which comes from the increase in the local electric field intensity of the composite film. This can be analyzed by Maxwell's electric field theory. The specific formula is as follows:

[0065] Formula (4)

[0066] In the formula, is the undisturbed electric field strength, and is the angular frequency of the electromagnetic wave, is the dielectric constant of the silver nanofilm, is the dielectric constant of the composite material, is the polarizability of the gold nanorods. Represents spatial coordinates.

[0067] When the concentration of gold nanorods increases, As the concentration of gold nanorods increases, the negative effect of this item is more significant, which is manifested as an increase in the local electric field intensity. At the beginning, when the concentration of gold nanorods is moderate, the absorption peaks between gold and silver nanoparticles are coupled with each other. This strengthening effect is obvious, and the intensity and width of the resonance peak are significantly increased compared with that of single Ag. However, as the concentration of gold nanorods increases further, the gap between the two metals decreases, resulting in weakened interaction and coupling, which also leads to a decrease in the intensity of the resonance peak. According to Maxwell's electric field theory, the local electric field intensity of the composite film is enhanced. This is because the increase in the dielectric constant increases the polarization ability of the internal charge of the material, thereby strengthening the local intensity of the electric field and increasing the intensity of the resonance peak. However, as the concentration of gold nanorods increases, the spacing between gold and silver particles gradually decreases. When the spacing decreases to a certain extent, the interaction and coupling between gold and silver particles begin to weaken, causing the antenna effect to disappear. When the distance between gold and silver nanoparticles is very small and can almost be regarded as a whole, the electromagnetic interaction of the composite material changes, and the resonance peak intensity decreases accordingly. The upconversion luminescence intensity of Au / UC composite film is enhanced by 1.12 times and 1.57 times at 521 nm and 540 nm respectively for green light, and 1.23 times at 653 nm for red light compared to single UC layer.

[0068] Example 6

[0069] Investigating the influence of Ag / Au / UC composite film on the luminescence intensity of upconversion materials

[0070] like Fig.11 The Ag / Au / UC composite film shown has an up-conversion luminescence intensity of 4.34 times and 4.87 times greater green light intensity at 521 nanometers and 540 nanometers, respectively, and a red light intensity at 653 nanometers, compared to a single UC layer. Compared to the gain produced by existing single precious metal composite films such as Examples 4 and 5, the enhancement amplitude of the present invention can reach about 3 times the existing level. The synergistic effect of gold and silver enhances the local electromagnetic field and promotes the generation of more excited state electrons, thereby increasing the intensity of up-conversion luminescence. This effect is attributed to the specific electromagnetic properties of gold-silver alloys, which complement each other in the SPR (surface plasmon resonance) effect, producing a synergistic effect that exceeds the sum of their individual effects.

[0071] At the same time, direct contact between the metal film and the UC film may cause a thermal effect, which may cause the temperature of UCNPs to rise, thereby increasing non-radiative transitions and causing fluorescence quenching. This thermal effect is mainly caused by the good thermal conductivity of the gold-silver alloy. Especially under high-power laser irradiation, the gold-silver alloy may absorb more heat energy, resulting in an overall temperature increase. In addition, gold nanorods have an extremely strong absorption peak at 980 nm, which completely overlaps with the emission peak of the upconversion material at 980 nm. This also causes the gold nanorods to absorb more energy, further increasing the temperature of the entire film. Therefore, temperature is also a factor that needs to be considered in practical applications. Fig.12 It can be observed that the Ag / UC composite film exhibits a faster temperature rise rate in the initial temperature rise stage and reaches a higher peak temperature than the UC single layer, which indicates that the addition of Ag significantly enhances the material's absorption of laser energy and thermal conversion efficiency. Specifically, the temperature of the UC layer gradually rises under laser irradiation, but the overall temperature change is small and the peak temperature is low. Fig.13 The FLIR temperature map shows that the temperature of the Ag / UC composite film rises rapidly to 30.9 °C and cools down quickly after the laser is turned off, showing a high thermal response speed and a large temperature difference, which may be related to the high thermal conductivity and good light-to-heat conversion efficiency of the silver layer.

[0072] For gold nanorod / silver / upconversion material composite films with different concentrations, the photothermal properties of the material increase with the increase of the concentration of the gold nanorod solution. Fig.12 It is shown in Figure 2 that when the concentration of gold nanorods is 0.2 mg / ml, 0.4 mg / ml and 0.6 mg / ml, the corresponding temperature curves reach peak temperatures of 38.2 °C, 40.9 °C and 44.1 °C, respectively. And as the concentration increases, the temperature rise rate accelerates. This shows that the introduction of gold nanorods further improves the photothermal conversion efficiency of the material. The higher the concentration, the greater the temperature rise. After comparative experiments, we finally selected a concentration of 0.15~0.25 mg / ml gold nanorods to balance the impact of the photothermal effect.

[0073] The materials and technologies mentioned in the examples, especially the doping and composite thin film technologies, have great application prospects for the development of efficient optoelectronic devices, bio-imaging and medical diagnosis. For example, doping-optimized upconversion nanocrystals can be used for highly sensitive bio-labeling and imaging, while the enhanced optical properties of gold-silver composite thin films can be used to improve the photoelectric conversion efficiency of solar cells.

[0074] Through synergistic enhancement and innovative preparation methods, the present invention not only improves the performance of the material, but also expands its application range in high-end optoelectronics and biomedicine, demonstrating its significant advantages in practical applications.

[0075] The practical application of the present invention in biomedical imaging benefits from its non-toxicity, high fluorescence efficiency and extremely narrow emission spectrum, showing excellent imaging quality in biological imaging and CT imaging. These nanomaterials have good biocompatibility and high water solubility, and do not require additional surface treatment. The fluorescence emission intensity is increased by about 10 times, providing new possibilities for biomedical imaging.

[0076] The unique optical properties of the invention make it particularly effective in anti-counterfeiting technology. 3+ ions, greatly enhancing the upconversion luminescence effect, achieving an advanced anti-counterfeiting technology that is efficient and difficult to imitate. This approach not only improves trademark security, but also enhances brand protection through unique visual effects.

[0077] The present invention can convert infrared light in the solar spectrum into a higher energy spectral region, thereby expanding the absorption range of solar cells. By converting near-infrared light into visible light and ultraviolet light, the photoelectric conversion efficiency of solar cells based on Sb2(S, Se)3 materials is greatly improved to 5.27%, which is more than 9.21% higher than that of traditional solar cells, and at the same time, it shows better long-term stability.

[0078] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for enhancing the luminous intensity of an upconversion material based on a composite thin film, characterized in that: The process comprises the following steps: coating a silver film on a glass electrode by vacuum evaporation technology, heating on a hot plate after the first annealing treatment, spraying with a gold nanorod solution to obtain a gold-silver composite film, and then evenly coating a layer of NaGdF4:Er on the gold-silver composite film by spin coating. 3+ / Yb 3+ Glowing crystals.

2. The method for enhancing the luminous intensity of an upconversion material based on a composite thin film according to claim 1, characterized in that: The NaGdF4:Er 3+ / Yb 3+ The preparation method of the luminescent crystal comprises: mixing gadolinium acetate, ytterbium acetate, erbium acetate and aluminum ions, heating the obtained mixed solution in an oil bath, adding a solution containing NH4F, NaOH and methanol to carry out a high pressure reaction, centrifugally washing and drying, and performing a second annealing treatment to obtain NaGdF4:Er 3+ / Yb 3+ Glowing crystals.

3. The method for enhancing the luminous intensity of an up-conversion material based on a composite thin film according to claim 2, characterized in that: The proportion of aluminum ions in the mixed solution is 13~17at.%.

4. The method for enhancing the luminous intensity of an up-conversion material based on a composite thin film according to claim 2, characterized in that: Gd in mixed solution 3+ , Yb 3+ , Er 3+ The molar ratio is 75~80:20:

2.

5. The method for enhancing the luminous intensity of an up-conversion material based on a composite thin film according to claim 2, characterized in that: Add oleic acid and octadecene into the mixed solution, and then heat it in an oil bath at a temperature of 130-170°C for 20-30 minutes.

6. The method for enhancing the luminous intensity of an upconversion material based on a composite thin film according to claim 2, characterized in that: The conditions of the high pressure reaction are 180-220° C., time 6-10 hours, and pressure 15-16 MPa.

7. The method for enhancing the luminous intensity of an up-conversion material based on a composite thin film according to claim 2, characterized in that: The first annealing treatment has a temperature of 70~90°C and a time of 0.5~1.5h; the second annealing treatment has a temperature of 240~260°C and a time of 1~3h.

8. The method for enhancing the luminous intensity of an up-conversion material based on a composite thin film according to claim 1, characterized in that: The concentration of the gold nanorod solution is 0.15-0.25 mg / ml.

9. An upconversion material based on a composite thin film, characterized in that: The method is prepared by any one of claims 1 to 8.

10. Use of the composite thin film-based upconversion material according to claim 9 in solar panels.